The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4187/respcare.04550
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Shared Canister Protocol for the Delivery of Metered-Dose Inhalers in Mechanically Ventilated Subjects

Abstract: BACKGROUND: Mechanically ventilated patients often need bronchodilators administered via a metered-dose inhaler (MDI).similar between the shared canister and single-patient canister groups. We did not observe clinically important differences for ventilator-associated events between study groups in our logistic regression analysis (P ‫؍‬ .07). There was a savings of $217/subject in the shared canister group due to the use of 299 fewer MDIs. CONCLUSIONS: Our study found that shared canister MDI therapy compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, a prospective trial demonstrated that a shared canister protocol for the delivery of MDIs was associated with a $40,000 cost savings without any differences in ventilator days, ventilator-associated pneumonias, or hospital mortality. 55 Although ventilator-associated events were noted to be more prevalent in the shared canister arm compared with the standard care arm, these findings are unclear because ventilator-associated events are more often used for surveillance at the population level rather than at the bedside. Nonetheless, although this approach may reduce waste, additional safety data on this approach as well as established infection control practices are needed prior to widespread implementation.…”
Section: Albuterol/ipratropiummentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a prospective trial demonstrated that a shared canister protocol for the delivery of MDIs was associated with a $40,000 cost savings without any differences in ventilator days, ventilator-associated pneumonias, or hospital mortality. 55 Although ventilator-associated events were noted to be more prevalent in the shared canister arm compared with the standard care arm, these findings are unclear because ventilator-associated events are more often used for surveillance at the population level rather than at the bedside. Nonetheless, although this approach may reduce waste, additional safety data on this approach as well as established infection control practices are needed prior to widespread implementation.…”
Section: Albuterol/ipratropiummentioning
confidence: 99%
“…Nonetheless, although this approach may reduce waste, additional safety data on this approach as well as established infection control practices are needed prior to widespread implementation. 55…”
Section: Albuterol/ipratropiummentioning
confidence: 99%
“…[ 209 ] In contrast, a recent study revealed that common canister protocol resulted in significant cost savings with similar rates of ventilator-associated pneumonia, mortality, as well as hospital length of stay, compared to single-patient pMDI. [ 210 ] Accordingly, each hospital should evaluate the risk–benefit ratio before following a common canister protocol. [ 25 ]…”
Section: Aerosol Therapy At Home: Education and Cleaningmentioning
confidence: 99%
“…14 Although pMDI use remains common during mechanical ventilation, there is ongoing contention regarding the use of shared (common) canister protocol versus single canister therapy. Gowen et al 21 found that common canister protocol does yield cost savings but may result in more ventilator-associated events. A study by Ari et al 14 suggested that the use of a vibrating mesh nebulizer during mechanical ventilation was superior to the use of traditional jet nebulizer with a 2-4-fold greater drug delivery, but there may be significant variance among certain models of vibrating mesh nebulizers affecting the overall consistency of dosing.…”
Section: See the Original Study On Page 391mentioning
confidence: 99%